God, the Bible, and Human Consciousness - Clasby, N. author. aut Link
XII, 255 p.
Keywords: This study offers a reading that avoids both literalism and sociological reductionism through a study of the Bible's intricate patterns of imagery. It will appeal to thoughtful people dissatisfied with the religious status quo and looking for a new intellectual starting point.